Building Brand Loyalty: Impact of Brand Awareness and Image on Wardah Cosmetics - Luthfi Gosan Ali; Febrianur Ibnu Fitroh Sukono Putra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The aim of this research to analyze influence of brand awareness and brand image to create brand loyalty empirical studies at Wardah Cosmetics. The population of this research is all students of Muhammadiyah University of Surakarta. The technique sampling in this research is convinience sampling by take 100 respondences. Data collection method using field study in form of personal questionnaire. Analysis tools in this research uses multiple linear regression. Based on the result are found some finding, the first is brand awareness has significant influence to create brand loyalty and the second is brand image has significant influence to create brand loyalty.